Lenin's Comintern Revisited - Riddell, John (Historical Materialism Book Series, 2026)
The Communist International (or 'Comintern') was launched in 1919 to promote worldwide extension of the 1917 workers' and peasants' revolution in Russia. During the Comintern's first years under the leadership of V.I. Lenin, it proposed and tested strategic and tactical concepts that retain their value and continue to be studied. While the Communist International was soon to be deformed and destroyed by the rise of bureaucracy and authoritarianism associated with Stalinism, its perspective on the fight for international revolutionary change still presents a compelling vision, and is an inspiring example for millions throughout the world.